Hypoxia-induced factor-1 alpha, vascular endothelial growth factor expression in BRCA1-related breast cancer: A prospective study in tertiary care hospital - Manisha Sharma; Sanjay Piplani; Manas Madan; Mridu Manjari; Saumil Garg; Komalpreet Kaur (Wolters Kluwer Medknow Publications, 2017)
Introduction: Breast cancer is the commonest cause of death among middle aged women. BRCA1 associated tumors carry a poor prognosis. Angiogenesis is considered necessary for tumor growth and for its metastasis. Hypoxia stimulates HIF-1α which then activates transcription of various proangiogenic cytokines like VEGF. In the present study we examined HIF-1α expression, sVEGF levels and BRCA1 mutations and their relation with clinicopathological parameters. We also determined whether the angiogenic markers have different role in angiogenesis in BRCA1 related cancers as compared to sporadic breast cancers. Materials and Methods: The study was conducted on 50 cases of breast cancer specimens. Histopathological typing and grading was done followed by immunohistochemistry for BRCA1 and HIF-1α. VEGF was done in the serum by ELISA. Results: All the tumors were infiltrating ductal carcinoma NOS. 16 cases were reported grade II and 34 cases as grade III. On immunohistochemistry, 27 cases showed BRCA1 positivity and HIF-1α was positive in 39 cases. sVEGF levels were increased in 21 cases (42%). BRCA1 positivity, HIF-1α expression and increased VEGF levels were significantly associated with higher grade and lymph node metastasis. There was significant correlation of BRCA1 positivity with increased HIF-1α expression (P = 0.009) and increased sVEGF levels (P = 0.005). Conclusion: Our findings suggest that BRCA 1 positive tumors have unique molecular profile and different mechanism of tumorigenesis. Such tumors are associated with increased HIF-1α expression and VEGF levels.